Associations of central obesity and habitual food consumption with saliva microbiota and its enzymatic profiles – a pilot study in Finnish children - Agrawal, Nitin; Fontana, Federico; Tarracchini, Chiara; Lommi, Sohvi; Ventura, Marco; Milani, Christian; Viljakainen, Heli (Frontiers in Microbiology, 2024)
Variation in diversity and composition of saliva microbiota has been linked to weight status, but findings have been inconsistent. Focusing on clinically relevant conditions such as central obesity and using advanced sequencing techniques might fill in the gaps of knowledge.We investigated saliva microbiota with shallow metagenome sequencing in children with (n=14) and without (n=36) central obesity. Additionally, we examined the role of habitual food consumption on microbial enzymatic repertoire.Data comprised 50 children (50% male) with a mean age of 14.2 (SD 0.3) years, selected from the Finnish Health in Teens (Fin-HIT) cohort. Dietary scores for consumption frequency of sweet treats (STI), dairy products (DCI) and plants (PCI) were derived based on a selfadministered food frequency questionnaire. Central obesity was defined based on waist-height ratio using the cut-off 0.5. Saliva samples were subjected to whole-metagenome shotgun sequencing, and taxonomic and functional profiling was achieved with METAnnotatorX2 bioinformatics platform.Groups had an average 20 (95% CI 14-27) cm difference in waist circumference. We identified the lack of Pseudomonas guguagenesis and Prevotella scopos, oulorum and oris as putative biomarkers associated with central obesity and observed a total of 16 enzymatic reactions differing between children with and without central obesity. DCI was associated with the highest number of enzyme profiles (122), followed by STI (60) and DCI (25) (Pearson correlation p < 0.05). Intriguingly, STI showed a high positive/negative correlation ratio (5.09), while DCI and PCI showed low ratios (0.54 and 0.33, respectively). Thus, the main driver of enzymatic reactions was STI, and the related pathways involved nitrate metabolism induced by Haemophilus parainfluenzae and Veilonella dispar among others.Clinically relevant differences in central obesity were only modestly reflected in the composition of saliva microbiota. Habitual consumption of sweet treats was a strong determinant of enzymatic reactions of saliva microbiota in children with and without central obesity. The clinical relevance of these findings warrants further studies.